Management of Zakat Collection through Digital Channels at BAZNAS of Padang City - Syndi Putri Harfianti; Putri Febri Wialdi (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Digital zakat collection represents BAZNAS of Padang City’s adaptation to digital public service delivery; however, the available payment channels remain underutilized because collections are dominated by civil servants, participation among non-civil servants is uneven, dedicated digital personnel are unavailable, and transaction recording depends on confirmation from muzakki. This study aims to analyze the management of zakat collection through digital channels at BAZNAS of Padang City and identify its supporting and inhibiting factors. A descriptive qualitative approach was employed, with informants purposively selected from BAZNAS officials, muzakki using digital channels, and non-civil servant community members who had not used these services. Data were collected through interviews and documentation and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that digital zakat collection is managed through planning, organizing, implementation, and supervision functions. Planning is guided by the Annual Work and Budget Plan and includes the provision of websites, QRIS, official bank accounts, mobile banking, and other digital channels, although specific digital collection targets have not been established. Organizational responsibilities remain distributed across several divisions without dedicated digital personnel. Implementation involves multiple digital payment and information channels, but utilization remains uneven, particularly among non-civil servant communities. Supervision is conducted through payment confirmation, bank-statement verification, transaction recording, and receipt issuance, although incomplete payment information continues to hinder administrative accuracy. Supporting factors include the availability of digital channels and information media, internal organizational support, and the increasing adoption of cashless transactions among muzakki. Conversely, limited human resources, the absence of specialized digital personnel, low public digital literacy, and insufficient participation by non-civil servant muzakki constrain implementation. The study concludes that effective digital zakat collection requires specific performance targets, dedicated personnel, integrated transaction-recording mechanisms, expanded digital literacy initiatives, and broader engagement with non-civil servant communities. These findings contribute to public management and digital philanthropy research by demonstrating how organizational capacity and community readiness shape the effectiveness of digital zakat services.